2022
DOI: 10.1101/2022.09.01.22279508
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mitochondrial dysfunction underlies cortical atrophy in prodromal synucleinopathies

Abstract: Isolated rapid eye movement sleep behavior disorder (iRBD) is a prodromal synucleinopathy characterized by several changes including brain atrophy. The mechanisms underlying atrophy in iRBD are poorly understood. Here, we performed imaging transcriptomics and comprehensive spatial mapping in a multicentric cohort of 171 polysomnography-confirmed iRBD patients and 238 controls with T1-weighted MRI to investigate the gene expression patterns and the specific neurotransmitter, functional, cytoarchitectonic, and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 85 publications
(138 reference statements)
0
7
0
Order By: Relevance
“…The locus coeruleus had no significant neuronal loss and gliosis but did have many Lewy bodies and Lewy neurites [20]. More recently, a large multicentric study found that genes involved in mitochondrial function and macroautophagy were the strongest contributors to cortical thinning occurring in iRBD [21].…”
Section: Irbd As a Prodromal Marker Of Synucleinopathymentioning
confidence: 99%
See 4 more Smart Citations
“…The locus coeruleus had no significant neuronal loss and gliosis but did have many Lewy bodies and Lewy neurites [20]. More recently, a large multicentric study found that genes involved in mitochondrial function and macroautophagy were the strongest contributors to cortical thinning occurring in iRBD [21].…”
Section: Irbd As a Prodromal Marker Of Synucleinopathymentioning
confidence: 99%
“…With regard to cortical GM, most of the studies reported decreased volume or thinning (Figure 2) in the frontal cortex [21,22,[24][25][26][27][28][29] in iRBD compared to healthy subjects. Also, the posterior temporal, parietal [29,47], dorsolateral prefrontal, orbitofrontal, occipital cortices [29,47,48] the superior frontal sulcus [25], the right superior frontal sulcus [27], and the dorsolateral primary motor cortex in the right hemisphere [22] were thinner or with a reduced volume.…”
Section: Grey Matter (Gm) Integritymentioning
confidence: 99%
See 3 more Smart Citations